Increased dNTP pools rescue mtDNA depletion in human POLG‐deficient fibroblasts. Issue 6 (8th March 2019) - Blázquez-Bermejo, Cora; Carreño-Gago, Lidia; Molina-Granada, David; Aguirre, Josu; Ramón, Javier; Torres-Torronteras, Javier; Cabrera-Pérez, Raquel; Martin, Miguel Ángel; Domínguez-González, Cristina; de la Cruz, Xavier; Lombès, Anne; García-Arumí, Elena; et al.
ABSTRACT: Polymerase γ catalytic subunit ( POLG ) gene encodes the enzyme responsible for mitochondrial DNA (mtDNA) synthesis. Mutations affecting POLG are the most prevalent cause of mitochondrial disease because of defective mtDNA replication and lead to a wide spectrum of clinical phenotypes characterized by mtDNA deletions or depletion. Enhancing mitochondrial deoxyribonucleoside triphosphate (dNTP) synthesis effectively rescues mtDNA depletion in different models of defective mtDNA maintenance due to dNTP insufficiency. In this study, we studied mtDNA copy number recovery rates following ethidium bromide‐forced depletion in quiescent fibroblasts from patients harboring mutations in different domains of POLG. Whereas control cells spontaneously recovered initial mtDNA levels, POLG‐deficient cells experienced a more severe depletion and could not repopulate mtDNA. However, activation of deoxyribonucleoside (dN) salvage by supplementation with dNs plus erythro ‐9‐(2‐hydroxy‐3‐nonyl) adenine (inhibitor of deoxyadenosine degradation) led to increased mitochondrial dNTP pools and promoted mtDNA repopulation in all tested POLG‐mutant cells independently of their specific genetic defect. The treatment did not compromise POLG fidelity because no increase in multiple deletions or point mutations was detected. Our study suggests that physiologic dNTP concentration limits the mtDNA replication rate. We thus propose that increasing mitochondrial dNTP availability could be of therapeutic interest for POLG deficiency and other conditions in which mtDNA maintenance is challenged.—Blázquez‐Bermejo, C., Carreño‐Gago, L., Molina‐Granada, D., Aguirre, J., Ramon, J., Torres‐Torronteras, J., Cabrera‐Pérez, R., Martín, M. Á., Domínguez‐González, C., de la Cruz, X., Lombès, A., García‐Arumí, E., Martí, R., Cámara, Y. Increased dNTP pools rescue mtDNA depletion in human POLG‐deficient fibroblasts. FASEB J. 33, 7168–7179 (2019). www.fasebj.org